PENGARUH PENDAPATAN ASLI DESA (PADESA), DANA DESA (DD) DAN BAGI HASIL (PAJAK DAN RETRIBUSI) (BHPR) TERHADAP BELANJA DESA BIDANG PENDIDIKAN (Studi Empiris Pada Desa se-Kabupaten Malang) - Fitri Yuni Ariska; Moh. Amin; Junaidi Junaidi (e_Jurnal Ilmiah Riset Akuntansi, 2021)
The purpose of this study was to determine the effect of Village Original Income, Village Funds and Profit Sharing (Taxes and Retribution) on Village Expenditures in the Education Sector in Villages in Malang Regency. Samples were selected using purposive sampling and obtained as many as 79 samples based on the applied criteria. This study uses multiple linear regression models. The results showed that Village Original Income, Village Funds and Profit Sharing (Taxes and Retributions) had a significant effect on Village Expenditures in the Education Sector in villages throughout Malang Regency. Village Original Income has a significant positive effect on Village Expenditures in the Education Sector in villages in Malang Regency. Village Funds have a significant positive effect on Village Expenditures in the Education Sector in villages in Malang Regency. Profit Sharing (Tax and Retribution) has no effect on Village Expenditures in the Education Sector in villages in Malang Regency.Keywords: PADESA, DD, BHPR and Village Expenditures in the Education Sector.